2018
DOI: 10.1177/2047487318763897
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and the risk of adverse cardiovascular events after an acute coronary syndrome

Abstract: Background The incremental prognostic value of assessing the metabolic syndrome has been disputed. Little is known regarding its prognostic value in patients after an acute coronary syndrome. Design and methods The presence of metabolic syndrome (2005 International Diabetes Federation) was assessed at baseline in SOLID-TIMI 52, a trial of patients within 30 days of acute coronary syndrome (median follow-up 2.5 years). The primary endpoint was major coronary events (coronary heart disease death, myocardial infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 40 publications
3
35
0
1
Order By: Relevance
“…Metabolic syndrome (MetS) is a constellation of cardiovascular risk factors that include abdominal adiposity, impaired glucose tolerance, hypertension, low serum high-density lipoprotein cholesterol and hypertriglyceridemia [1], and is associated with an eightfold increase in the risk of myocardial infarction (MI) [2]. Presence of MetS in patients with MI is associated with increased risk of adverse cardiovascular events and recurrent MI [3]. Obesity, especially abdominal adiposity is also considered an initial and principal pathophysiologic component of MetS [4].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome (MetS) is a constellation of cardiovascular risk factors that include abdominal adiposity, impaired glucose tolerance, hypertension, low serum high-density lipoprotein cholesterol and hypertriglyceridemia [1], and is associated with an eightfold increase in the risk of myocardial infarction (MI) [2]. Presence of MetS in patients with MI is associated with increased risk of adverse cardiovascular events and recurrent MI [3]. Obesity, especially abdominal adiposity is also considered an initial and principal pathophysiologic component of MetS [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, predictive risk factors are needed to allow clinicians to identify and monitor individuals at increased risk for developing type 2 diabetes. Numerous clinical trials and meta-analyses studies confirm that MetS, a cluster of risk factors or clinical and biological abnormalities [7], [8], demonstrates a significant relationship with cardiovascular disease and all-cause mortality [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous existing research studies have demonstrated the role MetS plays as a predictor of cardiovascular disease [12], [21]- [24] and reported that regardless of any clinical criteria or definition, it is the major outcome of cardiovascular disease [9], [14], [16]- [21]. Many reports have also confirmed a strong relationship between MetS and incident diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome (MetS) comprises of a cluster of risk factors that are related to glucose and lipid metabolism (obesity) as well as cardiovascular dysfunction (blood pressure) [109,110]. Recently, the prevalence of MetS health outcomes such as Type 2 diabetes are on the rise, posing a public health burden particularly in the developing world [111].…”
Section: Medicinal Properties Of Moringa Oleiferamentioning
confidence: 99%